THE LEADERSHIP OF THE SCHOOL IN DEVELOPMENT QUALITY CULTURE IN STUDENT LEARNING IN MTS STATE 2 MEDAN - Erniati Siregar, Syafaruddin, Muhammad Fuad Zaini (Universitas Dharmawangsa Medan, 2020)
The focus of research to describe the purpose of this study are: 1. To find out how Madrasa Head Leadership is in decision making, 2. To find out how Madrasa Head's efforts are in developing a quality culture in student learning in Madrasah Tsanawiyah Negeri 2 Medan. The research method used is a qualitative method with a case study approach. Then the results of the study showed that 1. Madrasah Head Leadership in decision making. The head of Madrasah at MTs Negeri 2 Medan is Transformational Leadership. namely making decisions by discussing Sarah with subordinates then building communication with subordinates and giving examples to subordinates.The efforts made by the head of Madrasah in developing a quality culture. The Principal of Madrasah MTs N 2 Medan carried out the development of culture, namely First, implementing the values of autonomy (independence) that are embraced by the academic community as a power source of quality spirit to answer all-time challenges through independent activities by madrasas in improving facilities and pre means